2016
DOI: 10.1002/bdrb.21178
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Stimulators, Intrauterine Insemination, and Assisted Reproductive Technologies Use and the Risk of Major Congenital Malformations—The AtRISK Study

Abstract: The use of ART and IUI was associated with an increased risk of major musculoskeletal and urogenital malformations. ART was associated with a higher risk of MCM compared to ovarian stimulators used alone. Even the adjustment, a contribution of the underlying subfertility problems cannot completely ruled out given the differences in the severity of subfertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
5
0
2
Order By: Relevance
“…These studies have also revealed an increased risk of intellectual disability and autism (Sandin, Nygren, Iliadou, Hultman, & Reichenberg, ). ART has been moreover linked to an increased risk of fetal growth restriction, low birth weight (Bloise, Feuer, & Rinaudo, ), congenital anomalies (Chaabane et al, ), premature birth and other perinatal complications (Pinborg et al, ) that could have consequences after birth. Several imprinting disorders have also been associated with ART, including the syndromes Angelman, Silver‐Russell, and Beckwith‐Wiedemann (Odom & Segars, ; Õunap, ).…”
Section: Long‐term and Transgenerational Effects Of Artmentioning
confidence: 99%
“…These studies have also revealed an increased risk of intellectual disability and autism (Sandin, Nygren, Iliadou, Hultman, & Reichenberg, ). ART has been moreover linked to an increased risk of fetal growth restriction, low birth weight (Bloise, Feuer, & Rinaudo, ), congenital anomalies (Chaabane et al, ), premature birth and other perinatal complications (Pinborg et al, ) that could have consequences after birth. Several imprinting disorders have also been associated with ART, including the syndromes Angelman, Silver‐Russell, and Beckwith‐Wiedemann (Odom & Segars, ; Õunap, ).…”
Section: Long‐term and Transgenerational Effects Of Artmentioning
confidence: 99%
“…10 Evidence-based findings showed that children conceived with ART were at an increased risk of major congenital malformations and low birth weight compared with children who had been spontaneously conceived. [11][12][13][14][15][16][17] However, most studies failed to observe this association within groups exposed to specific assisted methods and specifically among singletons. Studies focused on in vitro fertilization or inseminations or combined non-in vitro methods together, which has limited clinical implications.…”
mentioning
confidence: 99%
“…Malformations were classified according to the ICD-10 classification using Q-codes (Q00-Q99). Minor malformations (Q 10, Q16.2, Q17.0-17.9, Q18.0-18.2, Q18.4-18.9, Q25.0, Q27.0, Q38.1, Q51.5, Q51.6, Q52.0-Q52.7, Q53.0-Q53.9, Q66.3-Q66.6, Q69.0-Q69.9, Q70.0-Q70.9, Q81.0-Q81.9, Q82.1-Q82.9, Q83.0-Q83.9, Q84.0-Q84.9, Q85.0, Q86.0, Q95.0-Q95.2, Q95.4-Q95.5, Q95.9) were not included in the congenital malformation group [41].…”
Section: Data Collectionmentioning
confidence: 99%